2022
DOI: 10.3389/fphar.2022.825287
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Draining Lymph Node Reconstruction Promotes B Cell Activation During E0771 Mouse Breast Cancer Growth

Abstract: Lymph node metastasis is associated with tumor aggressiveness and poor prognosis in patients. Despite its significance in cancer progression, how immune cells in the tumor-draining lymph node (TDLN) participate in cancer immune regulation remains poorly understood. It has been reported that both anti-tumor and exhausted tumor-specific T cells can be induced in the TDLNs; however, B cell activation and maturation in the TDLN has received far less attention. In our studies using C57BL/6 mouse syngeneic E0771 bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 49 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…In a recent study, authors demonstrated that tDLNs from E0771 tumor-bearing mice undergo an intense morphological change following tumoral implantation. According to Louie et al tumor growth leads to the expansion of LN conduits in the B cell zone and disruption of the sub-capsular sinus (SCS) macrophage layer, favoring the transport of TAAs to GC zones and associated follicular dendritic cells (FDCs) 65 . Despite not assessing the kinetics of distinct B cell subsets through the weeks of tumor development, Louie et al reported the appearance of GC B cells in the tDLNs of the E0771 model as early as 7 days post-tumor implantation, indicating activation and proliferation of B cells in this site.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, authors demonstrated that tDLNs from E0771 tumor-bearing mice undergo an intense morphological change following tumoral implantation. According to Louie et al tumor growth leads to the expansion of LN conduits in the B cell zone and disruption of the sub-capsular sinus (SCS) macrophage layer, favoring the transport of TAAs to GC zones and associated follicular dendritic cells (FDCs) 65 . Despite not assessing the kinetics of distinct B cell subsets through the weeks of tumor development, Louie et al reported the appearance of GC B cells in the tDLNs of the E0771 model as early as 7 days post-tumor implantation, indicating activation and proliferation of B cells in this site.…”
Section: Discussionmentioning
confidence: 99%
“…While T cell-mediated immune response within TDLNs has received more attention, the role of B cells remains poorly understood. Nevertheless, a recent study conducted by Louie and colleagues has established a connection between tumor antigen-specific B cell maturation and tumor growth ( 205 ). Using B16F10 melanoma cells and a mouse model of breast cancer, the authors reported that tumors reconstructed TDLNs by disruption of the subcapsular sinus macrophage layer, which is a route for antigens to enter the germinal centers (GCs).…”
Section: Lymphatics and Immunity In The Context Of Cancer Immunotherapymentioning
confidence: 99%
“…Using B16F10 melanoma cells and a mouse model of breast cancer, the authors reported that tumors reconstructed TDLNs by disruption of the subcapsular sinus macrophage layer, which is a route for antigens to enter the germinal centers (GCs). Consequent entry of tumor-associated antigens into the GCs promoted B cell activation and maturation, which positively correlated with tumor growth and metastasis ( 205 ). While the role of B cells in cancer immunity remains controversial, this study highlights the connection between tumor progression in TDLNs and B cell activity, shedding light on future studies that may contribute to a deeper understanding of immunity within TDLNs and to the development of cancer immunotherapies.…”
Section: Lymphatics and Immunity In The Context Of Cancer Immunotherapymentioning
confidence: 99%
See 2 more Smart Citations